2021
DOI: 10.1177/23259671211064645
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Shoulder and Elbow Injuries in Baseball: A Scoping Review of 3 Types of Evidence

Abstract: Background: Shoulder and elbow overuse injuries are the most common problems in baseball players. No scoping review has compared the findings from different types of evidence. Purpose: To map the broad evidence from 3 types of evidence (epidemiological, biomechanical, and narrative) on potential risk factors for shoulder and elbow injuries in baseball and identify gaps in the existing literature to guide future research. Study Design: Scoping review. Methods: Eight electronic databases were searched from incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Medial elbow injuries are frequently observed in youth baseball players, accounting for 22.1-29.2% (19,28,40). Research has shown a link between baseball players' elbow injuries and abnormal ranges of shoulder rotation (30,37). Those risks are particularly concerning in youth players who may not have adequate resources for prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Medial elbow injuries are frequently observed in youth baseball players, accounting for 22.1-29.2% (19,28,40). Research has shown a link between baseball players' elbow injuries and abnormal ranges of shoulder rotation (30,37). Those risks are particularly concerning in youth players who may not have adequate resources for prevention.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 22 , 29 , 31 In a recent scoping review, Mine et al detailed risk factors for shoulder and elbow injuries in baseball and concluded that limited range of motion and field position were consistent risk factors for shoulder injury and being a pitcher or catcher were risk factors for elbow injuries. 19 In another systematic review, Hoppe et al concluded that nonmodifiable risk factors for shoulder injury include playing position and gender, while modifiable risk factors include shoulder rotation strength, scapular dyskinesis, and injury prevention program access. 13 However, these types of original research articles and ultimate reviews that focus on softball injury rates and preventions are largely lacking in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research reports that the prevalence of elbow pain among young pitchers is roughly 26% [16]. It has been postulated that pitchers, due to the significant physical demands placed on their upper limbs during play, suffer from an increased rate of elbow pain in comparison to their counterparts in other positions [17][18][19][20]. With the objective of improving the effectiveness and precision of our screening process, we strategically confined our examination to pitchers, catchers, and those players with a documented history of elbow issues.…”
Section: Discussionmentioning
confidence: 99%